Using a rubric to grasp intercultural competence development in vocational education. (2nd January 2021) - Gulikers, Judith; Brinkman, Dine; Runhaar, Piety
ABSTRACT: Worldwide, educational policies increasingly focus on students' intercultural competency development (ICD). But educational institutions struggle with its implementation due to difficulties concerning 1) explicating educational goals for ICD and 2) developing teaching, learning and assessment activities that foster this development. The paper describes the development of the Rubric ICD and two interlinked studies aimed to explore how this tool can help to explicate intercultural competence development in (higher) vocational curricula in the Netherlands. The first study, combining five teacher group interviews (n = 15), explores how the Rubric ICD helps to identify challenges and possibilities for explicitly integrating ICD in vocational curricula. The second study, involving 116 students going on international internships, examines if the Rubric ICD helps to explicate and examine students' thinking about ICD before and after their international internships. The studies showed that ICD is still mostly implicit in vocational curricula and students' learning. The Rubric ICD was found helpful for explicating ICD in various elements of vocational curricula and for reflecting on and coaching students' intercultural learning. The studies also revealed that teachers' professional development regarding ICD is needed and that the Rubric ICD could be helpful in that respect as well.